The Microstructure Properties of Ni-W Alloy Electrodeposition - Jaleel, Mofeed A.; Gurji, Eilaf Z. (Al-Nahrain Journal for Engineering Sciences, 2018)
The Electrodeposition process has been used to prepare Nickel-Tungsten alloys on low carbon steel substrate by using ammonical citrate bath. The influence of deposition condition by variation of current density (0.04-0.2 A/cm2) and solution temperature (60-70 °C), on the microstructure was studied. The optical microscope and the scanning electron microscopy (SEM) were used to study the morphology of the deposit while the energy dispersive spectroscopy (EDS) was used to approximate the composition, in addition to X-Ray diffraction examination. The results show that the current efficiency has the major influence on the tungsten content in the alloys due to the formation of ternary complex which reflected into the properties of the deposit._x000D_ Keywords: